THE DEVELOPMENT ATTRIBUTE VOLUNTEER BY THE SCOUT ACTIVITY OF BANPLAISOK SCHOOL UNDER SURATTHANI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Rittidat , Supatchai; PhrakhruKhemathammakhosit; Wiraponkan, Boonlert (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to: 1) study the characteristics of volunteerism among students at Ban Plai Sok School, 2) explore ways to develop volunteerism characteristics through Scout activities at Ban Plai Sok School, and 3) present and evaluate methods for developing volunteerism characteristics through Scout activities at Ban Plai Sok School. This is a qualitative research study, with data collected through in-depth interviews with 15 stakeholders, in-depth interviews with 5 experts, and group discussions with 7 qualified individuals. The tools used included interview and group discussion evaluation forms. The data were analyzed qualitatively using content analysis. The results of the study were as follows: 1) The characteristics of volunteerism among students at Ban Plai Sok School consisted of five components: (1) Gratitude: Some students need to be asked or assigned tasks before offering help. (2) Helping others: Some students only offered help when asked or when given direct instructions. (3) Sharing: Some students did not share things with others or only share with their own group. (4) Caring for communal property: Some students did not handle communal items carefully or properly store them after use. (5) Participation in activities: Students regularly participated in activities organized by the school or other agencies that benefit the school, community, and society. However, if the activity was a typical lecture, students may lose interest and not want to participate. 2) The approach to developing volunteerism characteristics through Scout activities at Ban Plai Sok School consisted of the following components: (1) Title, (2) Principles and rationale, (3) Objectives of the approach, (4) Implementation strategies, and (5) Monitoring and evaluation. The approach included 5 characteristics of volunteerism, which were: (1) Gratitude and thankfulness, (2) Helping others, 3) Sharing, 4) Taking care of public property, and (5) Participating in activities. The Scout activities consisted of 4 components: (1) Organizing Scout activities in the school based on the curriculum, (2) Scout ceremonies, (3) Special Scout subjects, and (4) Hiking and camping activities. 3) The presentation and evaluation of the approach to developing volunteerism characteristics through Scout activities at Ban Plai Sok School found that it was appropriate, feasible, and beneficial for use in developing volunteerism characteristics through Scout activities.